Etika Interaksi Guru dan Murid Menurut Perspektif Imam Al Ghazali - Indriyanti, Tri; Siregar, Khairil Ikhsan; Lubis, Zulkifli (Jurnal Studi Al-Qur'an, 2017)
The aim of this research is to describe and analyze the ethics of teacher and students interaction according to perspective of Imam Al Ghazali in the book called Ihya' Ulumuddin to develop the concept of ethics in the field of education and as an effort to next generation of nation that has an ethics that fits to the purpose of education. This research used qualitative descriptive approaches and type of research used literature or library research. This research concludes that according to Imam Al Ghazali in the book called Ihya umumuddin : a teacher must have an affection to the students, and imitate Rasulullah SAW in performing his teaching duties and intend to seek for Allah's pleasure. While the ethics of students interaction with the teacher according to Imam Al Ghazali : the students must purify their soul from the negative morals and natures before study, so that the knowledge they will learn can be useful and embedded to their soul, and only seek for the pleasure of Allah SWT in studying.